Long-term sedation with remimazolam besylate versus propofol in critically ill patients during invasive mechanical ventilation: a study protocol for a multicenter randomized non-inferior trial - Yang, Xiaobo; Tang, Yun; Du, Ruofei; Yu, Yuan; Xu, Jiqian; Zhang, Jiancheng; Liu, Hong; Zou, Xiaojing; Ren, Lehao; Yuan, Shiying; Shang, You (Frontiers in Pharmacology, 2023)
Background: Remimazolam besylate is a novel ultra-short-acting benzodiazepine that can potentially be a safe and effective sedative in intensive care units (ICUs). This study aims to assess whether remimazolam besylate is not inferior to propofol in maintaining mild to moderate sedation in critically ill patients receiving long-term mechanical ventilation. Methods and analysis: This is a multicenter, randomized, single-blind, propofol-controlled non-inferiority study. Eligible patients will be randomly assigned to receive remimazolam besylate or propofol in a 1:1 ratio to maintain a Richmond Agitation-Sedation Scale (RASS) score between -3 and 0. When patients are under-sedated, 2 rescue sedation of dexmedetomidine can be added. The primary outcome is the percentage of time in the target sedation range. The secondary outcomes are hours free from invasive ventilator in 7 days, successful extubation in 7 days, and weaning time, length of ICU stay, length of hospital stay, and mortality in 28 days. Modified intentionto-treat and safety analysis will be performed. Clinical trial registration number: https://clinicaltrials.gov/ct2/show/NCT05555667